Протестантська ортодоксія в етико-філософських концепціях ліберальної теології - Стасюк, Л. О.; Stasyuk, L. O. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті з’ясовано місце протестантської ортодоксії в процесах розвитку, зіткнення і перетину етико-філософських ідей теології М. Лютера, Ж. Кальвіна та представників ліберальної теології. Якщо ортодоксальні теологи лише загострюють увагу на проблемі співвідношення релігійного й морального, то в ліберальній теології відбувається етизація християнства, що призводить до формування нових, модерністських концепцій. For many centuries in spiritual life, the processes of evolution, transformation and internal differentiation religious philosophical systems are occurred. The article revealed place of Protestant orthodoxy in the process of development, conflict and crossing ethical and philosophical ideas of theology Luther, Jean Calvin and representatives of liberal theology. If orthodox theologians only focuses on the problem of religious and moral value, in liberal theology happens the etyzation of Christianity, leading the formation of new, modernist concepts. The author reveals the peculiarities of changes in the religious world of liberal theology, the essence of which lies in the understanding of Christianity as a Moral teachings.
Protestant Orthodoxy in the Ethical and Philosophical Concepts of Liberal Theology
Keywords: протестантська ортодоксія; Protestant orthodoxy; ліберальна теологія; liberal theology; мораль; moral; етико-філософські концепції; ethical and philosophical concepts; релігія; religion